Some Crucial Problems faces by Manokwari English Teachers - Riyanto, Edy Dwi (English Education Department, Universitas Islam Indonesia, 2007)
The case of Manokwari English teachers shows great challenge. There are at least two main problems: number and quality. The gap between the availability and the need of English teachers at Manokwari is huge. This rarity gives tremendous impact to quality. Some schools just picked any available teachers to teach English regardless the existence of their English background. This paper is aimed at (1) describing the condition of Papua English teacher especially from Manokwari regency, (2) offering some solutions for the condition.